Controlling active sites of Fe–N–C electrocatalysts for oxygen electrocatalysis. (December 2020) - Kim, Mi-Ju; Kim, Sungjin; Park, Ji Eun; Hwang, Chan-Cuk; Lee, Seunggyeong; Kang, Sun Young; Jung, Daesung; Cho, Yong-Hun; Kim, Jaekook; Lee, Kug-Seung; Sung, Yung-Eun
Abstract: The electrochemical oxygen reduction reaction (ORR) is a critical reaction in many energy conversion and storage systems, including fuel cells and metal–air batteries. Nonprecious-metal-based catalysts have captured attention for realizing viable and sustainable devices. However, in Fe-based catalysts, the efficient utilization of active sites, Fe–Nx and Fe coated on a carbon layer (Fe@C), is challenging owing to difficulties in controlling these active sites during synthesis. In this study, FeNC electrocatalysts with varying Fe/C ratios show different Fe@C/Fe–Nx ratios and ORR activities. Increasing the carbon content increases the Fe–Nx site density while decreasing the size of the Fe nanoparticles and the thickness of the carbon coating layer, thus enhancing the ORR activity. As cathode materials for anion exchange membrane fuel cells and Zn–air batteries, the FeNC electrocatalysts exhibit excellent performance when compared to Pt catalysts and previously reported transition-metal-based catalysts. Based on the structural changes observed by in situ X-ray absorption fine structure analysis during electrochemical operation, these catalysts were found to contain electrocatalytically efficient Fe–N4 sites. This work provides efficient strategies for designing high-performance catalysts for the ORR. Graphical abstract: Image 1 Highlights: High-performance ORR catalysts with both Fe@C and Fe–N4 active sites are prepared. Synergetic effect of Fe@C and Fe–N4 sites improved catalytic activity. Anion exchange membrane fuel cell with the catalysts showed high performance. Zn-air battery utilizing the catalysts also exhibited high performance. In situ XAFS analysis revealed that Fe–N4 sites are catalytically efficient sites.